Study on the settlements composition of Tana Toraja and Mamasa Toraja in Sulawesi, Indonesia - Pascarianto Putra Bura; Tetsuya Ando (Journal of Asian Architecture and Building Engineering, 2024)
This study aims to clarify the characteristics of settlement composition and house layout in Mamasa Toraja and Tana Toraja, Indonesia, focusing on spatial differences. The study reviewed relevant literature, selected settlements for the survey, and prepared settlement layout maps based on satellite imagery. Field surveys were conducted in 2022 to revise the settlement layout maps, record house plans, and interview local residents. The study found that despite having the same cultural roots, Tana Toraja and Mamasa Toraja have different settlement configurations and house layouts. The Tana Toraja settlements have a straight composition with warehouses on the north side and houses on the south side, flanked by a street-like plaza. In contrast, the composition of Mamasa Toraja settlements in the mountainous area is curvilinear, following the natural topography. Although social restrictions based on the caste system have long since been abolished, the layout of houses in the Toraja settlement, especially in Mamasa, still shows a social structure from when the caste system existed. This study provides insights into the unique spatial forms and cultural practices of the traditional villages in Mamasa Toraja and Tana Toraja, highlighting the importance of preserving their cultural heritage.